Flavonoid Quantification in Fruits and Seeds of Momordica charantia L. by UV-Vis Spectrophotometry - Novia Ardana F. Hamim; Dewi Yuliana; A. Muflihunna; Faradiba Abdul Rasyid; Rahmawati Rahmawati; Rezki Amriati Syarif (Journal of Experimental and Clinical Pharmacy (JECP), 2026)
Momordica charantia L. (bitter melon) is a medicinal plant widely recognizedfor its bioactive compounds, particularly flavonoids, which exhibit potentantioxidant properties. This study aimed to quantify the total flavonoidcontent in the fruits and seeds of M. charantia using UV-Visspectrophotometry and quercetin as a standard compound. Samples wereextracted with 70% ethanol and analyzed by the aluminum chloride–potassium acetate colorimetric method at the specific absorptionwavelength, using quercetin as the standard. The results demonstrated thatthe fruit's average flavonoid content was 2.261 mg QE/g extract, whereasthe seeds contained 2.906 mg QE/g extract. These findings indicate that theseeds possess the same flavonoid concentration as the fruit, highlightingtheir potential as a valuable natural source of antioxidant compounds.